Physical properties of alkali metals-based iodides via Ab-initio calculations. (September 2019) - Mahmood, Q.; Noor, N.A.; Rashid, Muhammad; Haq, Bakhtiar Ul; Laref, A.; Qasim, Irfan
Abstract: Methods based on density functional theory are used to evaluate the thermodynamic, mechanical, optoelectronic and thermoelectric properties of the alkali metal-based iodides: XGeI3 (X = K, Rb and Cs). The thermodynamic stability of these compounds is checked by negative formation energy, and mechanical stability tested through tensor analysis of Chapin's method. For optoelectronic and thermoelectric properties, the recently developed modified Becke–Johnson potential is applied for accurate analysis of bandgap values. The optical properties are explored in terms of dielectric constants and refraction, while thermoelectric properties are explained by electrical and thermal conductivities, Seebeck coefficient, power factor and figure of merit scale. The narrow bandgap, high value of light absorption in the visible region and thermoelectric efficiency make XGeI3 prospective materials for renewable energy applications. Highlights: We elucidate physical properties of alkali metal-based iodides [XGeI3 (X = K, Rb, and Cs)]. We confirm thermodynamic stability of studied compounds by enthalpy of formation. Thermoelectric properties of spinel oxides determined using BoltzTraP code. Narrow bandgap and thermoelectric efficiency give XGeI3 potential in renewable energy applications. These materials are suitable for use in thermoelectric devices.